Sanger Coffee: between Cultural Media and Diplomacy - Alam, Saidul; Nasution, Muhammad Mahruf; Pohan, Syafruddin (Budapest International Research and Critics University, 2021)
This study describes the Sanger Coffee which is between cultural media and diplomacy. This research uses descriptive research with a qualitative research approach. The research locations taken were several coffee shops around Jalan Doctor Mansur, Padang Bulan, Medan City. The unit of analysis in this study is Sanger Arabica in coffee shop media and diplomacy. The key informants in this research are people who form diplomacy in coffee shops and additional informants are people who form social networks in coffee shops around Padang Bulan Village. Data analysis using data interpretation techniques. The results of the study show that when people consume Sanger Coffee in a coffee shop, it becomes a place for free discussion by the community about the current socio-political and cultural conditions that occur around the community. In addition, Sanger Coffee is used as a tool to express oneself and create a micro network social for coffee shops.